1987
DOI: 10.1101/gad.1.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Relative position and strengths of poly(A) sites as well as transcription termination are critical to membrane versus secreted mu-chain expression during B-cell development.

Abstract: Re1at1ve p051t10n and 5tren9th5 0f p01y(A) 51te5 a5 we11 a5 tran5cr1pt10n term1nat10n are cr1t1ca1 t0 mem6rane ver5u5 5ecreted 1x-cha1n expre5510n dur1n9 8-ce11 deve10pment 6a6r1e11a 6a111,1 Jeffrey W. 6u15e, 2 M1chae1 A. McDev1tt, 1 Ph111p W. 7ucker, ~ and J05eph R. Nev1n51 1H0ward Hu9he5 Med1ca1 1n5t1tute, 7he R0ckefe11er Un1ver51ty, New Y0rk, New Y0rk 10021 U5A; 2Departrnent 0f M1cr0610109Y, 50uthwe5tern Med1ca1 5ch001, Un1ver51ty 0f 7exa5 Hea1th 5c1ence Center, Da11a5, 7exa5 75235 U5A Dur1n9 8-ce11 d1ffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 26 publications
3
78
2
Order By: Relevance
“…In immature B cells and mature B cells, the membrane mRNA form is produced, and the secretory poly(A) site is inactive (Lamson and Koshland 1984). Upon differentiation, the secretory poly(A) site is activated and the secretory form of mRNA is expressed (Galli et al 1987(Galli et al , 1988Peterson et al 1991;Takagaki et al 1996). In addition, the secretory mRNA's stability is increased (Mason et al 1988;Cox and Emtage 1989).…”
Section: Introductionmentioning
confidence: 95%
“…In immature B cells and mature B cells, the membrane mRNA form is produced, and the secretory poly(A) site is inactive (Lamson and Koshland 1984). Upon differentiation, the secretory poly(A) site is activated and the secretory form of mRNA is expressed (Galli et al 1987(Galli et al , 1988Peterson et al 1991;Takagaki et al 1996). In addition, the secretory mRNA's stability is increased (Mason et al 1988;Cox and Emtage 1989).…”
Section: Introductionmentioning
confidence: 95%
“…By moving elements of the gene around, thus changing the length of the intron between μS and μM exons, the Nevins and Tucker groups (Galli et al 1987(Galli et al , 1988 concluded that the choice was not due to proteins in plasma cells (plasmacytoma cells) and mature B cells (lymphoma cells) that dictated splice choice because plasmids that contained only one of the two 3 ′ terminal exons and polyA sites were expressed equally. The DSX pre-mRNA transcript is processed differently in females and males.…”
Section: Immunoglobulin Chains: Mμm and Mμs Chainsmentioning
confidence: 99%
“…Two types of experiments strongly suggested that the poly(A) site switch does not require any gene-speci¢c factor. In one experiment it was shown that the switch operated only when the two poly(A) sites competed in the same pre-mRNA but not when they were located in di¡erent transcription units [95,96]. In the second type, a gene was built that contained a similar arrangement of alternative splice and poly(A) sites as the IgM heavy chain gene, but was composed of di¡erent sequences.…”
Section: Regulatory Aspectsmentioning
confidence: 99%